Rice-Field Pond Systems for Food and Resilient Livelihoods - Sean, Vichet; Mam, Kosal; Akester, Michael; Wardell, David (WorldFish, 2025)
Cambodia’s ricefield ponds are small water bodies within or near rice fields that provide multiple benefits beyond water storage. They serve as fish refuges during dry spells, support pest control, and create opportunities to integrate fish, rice, vegetables, and livestock into one climate-smart farming system. Research in Takeo and Prey Veng has shown that improved pond management can boost fish production by 67%, enhance biodiversity, and provide two crop cycles, leading to greater income and resilience for farming households. However, challenges remain, including water shortages in the dry season, limited feed, pesticide use, and gaps in farmer knowledge, which can be addressed through better pond design, integrated pest management, low-cost supplementary feed, and farmer-to-farmer learning.